SUPERCONDUCTIVITY AND THE METAL-SEMICONDUCTOR TRANSITION IN THE SEPTENARY OXIDE SYSTEM, (TL0.5PB0.5)(CA1-YYY)SR2CU2O7-DELTA - Liu, R; Edwards, P; Huang, Y; Wu, S; Wu, P (1990)
The septenary compound (Tl0.5Pb0.5)(Ca1-yYy)Sr2Cu2O7-δ exhibits the highest superconducting transition temperature (110 K) yet observed in the TlCaBa2Cu2O7-δ (1122) structure type. This complex, six-blend combination of metallic elements which make up the material is, however, compensated by a relatively simply crystal structure, which bears many similarities to that of 90 K superconductor YBa2 Cu3O7-δ. In this note we report some important features of the cation-substitution chemistry of the title compound, drawing attention to the fundamental changes in the electronic properties of the (Tl0.5Pb0.5) (Ca1-yYy)Sr2Cu2O7-δ system as Ca2+ is replaced by Y3+. Superconductivity is observed over the homogeneity range y = 0-0.5, with the superconducting transition temperature showing a maximum (108 K) at y = 0.2. Across the homogeneity range y = 0.6-1.0, the material undergoes a metal-semiconductor transition. © 1990.